A comparison of automated auditory brainstem response (AABR) with integrated electrodes and otoacoustic emissions (OAEs) in high risk newborn hearing screening - Ramli, Muhammad Noor Azmi (2017)
OBJECTIVE To compare the outcome between AABR (by using MB11 BERAphone method) and Integrated Electrodes and Otoacoustic Emissions (OAEs) in high risk newborn in Hospital Universiti Sains Malaysia. METHODS This is an observational study which is a cross-sectional study design involving two methods in the same subject. A total of 195 high risk newborn and who have fulfilled the inclusion and exclusion criteria will be participate in our study. These high risk babies were subjected to OAEs and followed by an MB11 BERAphone screening test at the same setting as near to discharge as possible or once the patient is stable enough to do a hearing screening. Both instruments produced a “pass” or “refer” result and did not require any special skills for the interpretation of results. The “refer” result from OAEs and MB11 BERAphone will be screened using ABR to determine the false positive. The time will be measured by total staff time spent on each instrument. To minimise the measurement bias, two testers will be used to handle both screening methodsRESULTS There were 195 newborns (87, 44.6% boys and 108, 55.4% girls) who participated in this study. Ototoxic medication was the most common risk factor (51.8%) followed by hyperbilirubinaemia (51.3%), and birth weight <1500g (27.2%). MB11 BERAphone had a higher passing rate (89.8%) as compared to OAEs (85.2%). MB11 BERAphone had a lower refer rate (10.2%) compared to OAEs (14.8%). These differences are statistically significant. The true negatives are MB11 BERAphone (29.4%) and OAEs (11.8%). False negative MB11 BERAphone (5.9%) and OAEs (0.0%). Out of 195 newborns examined, 182 (93.4%) showed agreement between the two techniques, whereas in 13 (6.6%) there was no agreement. Interobserver agreement was good (kappa = 0.698, p=<0.001). The median test time that was done for each newborn using MB11 BERAphone was 5 minutes (IQR: 25th-75th) and OAEs was 2 minutes (IQR: 25th-75th). The difference were statistically significant (p = <0.001). CONCLUSION The MB11 BERAphone is still a reliable device for auditory brainstem response among high risk newborn hearing screening. In the presence of false negative in MB11 BERAphone, it might not really be significant in this study due to a few factors affecting the result. Both agreements were good. However, the duration of time for hearing screening for each newborn took a significantly longer time compared to OAEs. Therefore, we recommend that both methods can be used as a first screening, followed by a screening using ABR for those whose result was “refer” from the first screening.